A Study of the Differences among EFL/ESL Methods for Reading Comprehension and Language Awareness - NÚÑEZ VÁZQUEZ, ISABEL; CRISMÁN PÉREZ, RAFAEL (Porta Linguarum Revista Interuniversitaria de Didáctica de las Lenguas Extranjeras, 2021)
The present paper reports on the effectiveness of the Grammar-Translation Method, Communicative Language Teaching and Content and Language Integrated Learning upon reading comprehension and language awareness. The study recruited a convenience sample of 164 Spanish students from a rural area in southern Spain who randomly received these three ESL/EFL methods. The research was focused on two hypotheses. Firstly, L2 reading learning is more effective from CLT and CLIL than GTM despite of being visual skills the main core of translation methods. Secondly, CLT and CLIL demand more contextual learning, so these methods consider pragmatic awareness more relevant than GTM. Results showed CLT method offered more similar results among the reading comprehension tasks (p<.01). However, from a descriptive study, GTM obtained the best performance globally. Pragmatic awareness performed the weakest area among all three methods. However, the interaction between reading comprehension and language awareness suggested that the intervention was more supportive for CLT. Also, significant intra-gender differences according to the learning methodology were provided. Study limitations and future research recommendations also were discussed.